Tourism development impacts, cultural intelligence and community support for future development - Siti Aishah Zakaria; Muaz Azinuddin; Hawa Husna Ab Ghani; Wan Mohd Adzim Wan Mohd Zain; Nur Shahirah Mior Shariffuddin; Mohd Hafiz Hanafiah (Tourism and Hospitality Management, 2024)
Purpose – This study examines the dynamics of cultural intelligence (CQ) on the tripartite tourism development impacts (TDI) in the economic, social and environmental domains and how it influences residents’ perceptions of tourism development. Methodology/Design/Approach – Using a quantitative cross-sectional research design and random sampling, three hundred and forty-one (341) responses were analysed using partial least Square-Structural Equation Modelling (PLS-SEM). Findings – The study confirms that the TDI dimensions (economic and social) have a positive influence on CQ, while environmental impact is an insignificant determinant. CQ also significantly mediates the relationship between TDI (economic and social impact) and SFTD. Similar to the insignificant direct effect, CQ does not mediate the relationship between environmental impact and SFTD. Originality of the research – This finding suggests that cultural intelligence plays a crucial role in shaping community attitudes and receptivity to future tourism development projects. Furthermore, the result of this study emphasises the uniqueness of the influence of the different TDI dimensions on community support and the urgency of addressing economic and social concerns in tourism development.